GERAKAN REFORMASI PROSTENTATISME DALAM SEJARAH GEREJA KATOLIK - Edison R.L Tinambunan (Litbang STFT Widya Sasana Malang, 2017)
This year (2017) is the anniversary of 500th of Protestantism. This celebration is commemorated by either Catholic or Protestant with the different accentuation. This article is not intended to show the right or wrong side but to analyze the historical realities, which could be accepted by both Catholic and Protestant. The reality shows that the emergence of Protestant did not happen in a short period or only on decades, but it took ages (few centuries). The freedom of Christian which was given by Constantine on 312, created positive impact to the Church quantitatively. However, it was not accompanied with the quality of the people’s life. The society, politic and culture were unfortunately influenced the Church negatively. One of the great influences was the degradation of morality. The level of morality of the Church at that time was the lowest during its journey. Efforts to recover from this situation of the Church was performed by many Christians with the intention to “be back to the sources”, which regenerated eremitism and the birth of Mendicant Orders. Nevertheless, these movements could not stem the situation of the Church. One of the toughest difficulties was feudalism. The intent of the renewal movement of the Church raised many protests from theologians, such as John Wycliffe, Jan Hus and Martin Luther. Martin Luther’s protest was the climax and brought the biggest schism in the Church history. Martin Luther’s movement is, then, followed by many reformists which is continuing up to this time. Tahun ini (2017) adalah peringatan protestantisme yang ke-500 tahun. Perayaan ini dikenang oleh pihak Katolik atau Protestan dengan aksentuasi yang berbeda. Artikel ini tidak dimaksudkan untuk menunjukkan sisi benar atau salah, tetapi untuk menganalisis realitas historis, yang diterima oleh pihak Katolik dan Protestan. Realitas menunjukkan bahwa desakan dari Protestan tidak terjadi dalam periode yang singkat atau hanya dalam satu dekade, tetapi terjadi dalam suatu masa (beberapa abad). Kebebasan Kristiani yang diberikan oleh Konstantinus pada tahun 312 mengakibatkan dampak yang positif bagi Gereja secara kuantitatif. Bagaimanapun, itu tidak disertai dengan kualitas hidup banyak orang. Sosial, politik dan budaya secara tidak menguntungkan dipengaruhi Gereja secara negative. Salah satu dari pengaruh-pengaruh yang besar adalah degradasi moralitas. Tingkat moralitas dari Gereja pada waktu itu paling buruk selama peziarahannya. Usaha untuk memperbaiki situasi Gereja tersebut ditunjukkan oleh banyak orang Kristen dengan intensi untuk “kembali kepada sumber”, yang memperbaharui pesan eremitisme dan Mendikantes. Meskipun demikian, pergerakan-pergerakan tersebut tidak dapat mengatur situasi Gereja. Salah satu kesulitan yang paling buruk adalah feodalisme. Tujuan dari pergerakan pembaharuan dari Gereja membangkitkan banyak protes dari kalangan teolog, seperti John Wycliffe, Jan Hus dan Martin Luther. Protes Martin Luther adalah klimaks dan membawa skisma yang paling besar di dalam sejarah Gereja. Gerakan Martin Lutherdiikuti oleh banyak reformis yang masih berlanjut sampai saat ini.